Pengaruh Motivasi Kerja, Disiplin Kerja Dan Learning Organization Terhadap Kinerja Karyawan PDAM Tirta Musi Palembang Unit 3 Ilir - Ketut Reki; Mukran Roni (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this research is to find out the influence of work motivation, work discipline and learning organization on the performance of PDAM Tirta Musi Palembang Unit 3 Ilir employees. The data collection technique used in this research is using a questionnaire method with closed questions so that respondents choose the answers that have been provided and the analysis method used is Multiple Linear Regression Analysis. The results of this research are that the variables Motivation, Work Discipline, and Learning Organization influence employee performance. Based on the f test results of 0.022, the value of 0.022 is smaller than 0.05, so it can have an influence on employee performance. Increasing high employee performance is very important in a company, because with high employee performance it will be possible to increase employee work productivity. With increased productivity, the company's goals will be achieved automatically. Therefore, a company always tries to improve the performance of its employees, so that the company's goals can be achieved immediately. Factors that can influence performance itself are motivation, employee work discipline, and learning organization.